Is the Climate of Hyderabad becoming Drier? - Singh, S. N. (Indian Forester, 1978)
Seventy two years meteorological data (from 1901 to 1972) have been analysed to find out whether the climate of Hyderabad is shifting towards drier side. The water balance and aridity indices for four yearly blocks and for eleven yearly blocks (following the sun-spot cycles) have been computed. The analysis reveals that there is no significant evidence that climate of Hyderabad is becoming drier.